SPE Annual Technical Conference and Exhibition 2015
DOI: 10.2118/175029-ms
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Drawdown Sensitivity in Shale Reservoirs Using Coupled-Geomechanics Models

Abstract: Productivity loss in some shale reservoirs is often attributed geomechanics-related factors, even when the exact mechanism(s) is undetermined. Overpressured reservoirs tend to experience a large increase in effective stress during depletion, which can contribute to a dramatic loss in fracture conductivity. Factors such as a low elastic modulus may also contribute to productivity loss through processes such as proppant embedment. The Haynesville Shale (Texas and Louisiana) is often cited as an example of geomec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Even after the stress is restored, the permeability can only recover to 10–15% of the initial state. 33 …”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even after the stress is restored, the permeability can only recover to 10–15% of the initial state. 33 …”
Section: Results and Discussionmentioning
confidence: 99%
“…Even after the stress is restored, the permeability can only recover to 10−15% of the initial state. 33 Wilson et al 33 proposed a single-fracture numerical model with different maximum horizontal in situ stress distribution orientations to study the influence of pressure drop strategy on the ultimate recoverable reserve (EUR). The research results show that by alleviating the impact of effective stress on the natural fracture compaction, the reasonable pressure drop scheme can increase the EUR by 15%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Sw within NF is relatively high (17%) for the base case, which limits the flow of oil in NF. However, the oil production gap between three models is not large because tight reservoirs do not require very high fracture conductivity, and proppant that is evenly distributed within a fracture should be more important for well productivity [64]. From Figure 11, it can be found that the oil phase appears in NF after one day of flowback, when stress-dependent porosity is absent.…”
Section: Impact Of Fracture Closurementioning
confidence: 99%
“…Formulating a reasonable pressure-controlled production plan is the key to obtaining ideal productivity of over-pressured fractured shale gas reservoirs. The common research methods for the dynamic performance analysis of shale gas wells with pressure drawdown management mainly includes: field test 11 , physical simulation [12][13][14] , and numerical simulation 11,15,16 . Restricted to the strong regionality and high research costs, field tests are mostly used in large-scale field tests to provide engineering practice knowledge for theoretical scientific research and physical simulation work.…”
mentioning
confidence: 99%